PERAN DISPORA PROVINSI RIAU DALAM MENINGKATKAN PRESTASI ATLET PUSAT PENDIDIKAN DAN LATIHAN OLAHRAGA PELAJAR (PPLP) - Aldian Jatmoko; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The role of the Riau Provincial Youth and Sport Office is to step up the sport gradually through various sports activities management, one of which establishes the Center for Education and Training of Student Sports (PPLP) as a forum for the education and coaching of talented student athletes which is a manifestation of the system of manifestation of the mandate of Law Number 3 In 2005 about the National Sport System in creating the seeds of prestigious sporting achievements. Each year there is a national championship between PPLP, this activity is part of a tiered and sustainable nationwide sports competition system. Each year there is a national championship between PPLP, this activity is part of a tiered and sustainable nationwide sports competition system. The purpose of the national championship between PPLP is as the peak coaching of sports achievement of learners and evaluation of various forms of PPLP coaching.The method used in this study was conducted by qualitative approach with descriptive method, with data collection techniques including observation, interview, documentation study related to research objectives. Instrument in this study refers to the theory that Mulyasa (2002) explained that in an organization can not be separated from the roles and managerial aspects that are closely related to the role that is implemented, namely planning, coordinating, processing information for decision making, and evaluation.The results showed that Riau Dispora's role in supporting, facilitating and managing went well. However, the role of Dispora of Riau Province in coordinating the regional unit (athletic branch / Dispora of the city / regency) in Riau Province, athletic club, in order to identify local athletes to find new seeds from the talent that has been owned is still very minimal, most selected athletes originated Or center of selection and coaching athletes focused on students in the city of Pekanbaru. Constraints or factors that inhibit the role of Riau Province Dispora, among others; The limited ability of the local government to fund sports, the lack of facilities and infrastructure, such as health facilities and physical exercise support equipment, and the lack of roles of the regional branch athletics branch or Dispora Regency / City in Riau Province.Keywords: Role, Sports Exercise, Coaching, Athlet.